Energy-efficient operation of a direct air-cooled condenser based on divisional regulation. (December 2021) - Luo, Zhiling; Liu, Jizhen; Huusom, Jakob Kjøbsted
Highlights: A scaled-down platform is established to study the cluster effect and fan partition scheme. Experimental data is utilized to calculate the divisional cluster factor of fans. An energy-efficient operation strategy based on divisional regulation is proposed. Abstract: The aerodynamic behavior of the fans array of the direct air-cooled condenser is different from that of a single fan because of the interaction effect between fans and the influence of wind. In this paper, a scale-down fan array experimental platform with measurement of the airflow and ambient wind speed is established to study the fan array partition schemes and cluster effect. The divisional cluster factors are obtained by experiment and generalized by random forest regression. The dynamic models of the condenser backpressure are introduced by the moving-boundary method. To achieve transient performance, a divisional control strategy for the direct air-cooled condenser is realized by MPC-PID cascade control. The simulation result shows that the fan power consumption is reduced by 14.7% compared to the existing control strategy. Furthermore, the wind speed disturbance is quickly suppressed by cascade control.